Connectivity, contest and the ties of self‐management support for type 2 diabetes: a meta‐synthesis of qualitative literature. (1st October 2015) - Foss, Christina; Knutsen, Ingrid; Kennedy, Anne; Todorova, Elka; Wensing, Michel; Lionis, Christos; Portillo, Mari Carmen; Serrano‐Gil, Manuel; Koetsenruijter, Jan; Mujika, Agurtzane; Rogers, Anne
Abstract: This paper presents a meta‐synthesis of the literature on community‐based self‐management to support experiences of people diagnosed with type 2 diabetes. The aim was to synthesise findings on both formal and informal self‐management support with particular reference to the relevance and influence of the social context operating at different levels. The review forms part of EU‐WISE, a project financed through EU's 7th Framework Programme. The review was performed by systematically searching MEDLINE, PubMed, EMBASE, CINAHL, PsycINFO and Web of Science for English language publications between 2005 and 2014 presenting research conducted in Europe on the experiences and perspectives of self‐management concerns of patients diagnosed with type 2 diabetes. The search yielded 587 abstracts, which were reduced through search strategy refinement and eligibility and quality criteria to 29 papers that were included in the review. This review highlights the relevance of contextual factors operating at micro‐ and macro‐levels. The synthesis yielded six second‐order thematic constructs relating to self‐management: sense of agency and identity, the significance and meaning of social networks, minimal disruption of everyday life, economic hardship, the problem of assigning patients' responsibility and structural influences of primary care. Using a line of argument synthesis, these themes were revisited, and a third‐order construct, connectivity emerged which refers to how links in daily life are interwoven with peoples' social networks, local communities, economic and ideological conditions in society in a way which support self‐management activities. This meta‐synthesis indicates a need to heed the notion of connectivity as a means of mobilising and supporting the self‐management strategies of people with type 2 diabetes in everyday life.